The current state of adjustment of maintenance systems to the conditions of Industry 4.0 - Trzcieliński, Stefan (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The Idea of Industry 4.0 has been known since 2011. It is currently being developed by its specific technologies regarding automation and data exchange in value chain. To maintain of these technologies in readiness for their exploitation creates a new challenge in terms of adapting systems used by maintenance departments to the conditions of Industry 4.0. The purpose of this article is to check to what extent maintenance systems and practices used in enterprises operating in Poland are close to preventive maintenance, which is considered appropriate for Industry 4.0. To achieve this goal, empirical research was conducted on a sample of 100 medium and large enterprises operating in Poland, regarding the adaptation of these enterprises to the conditions of Industry 4.0. Data was obtained by means of an interview questionnaire, with respondents being managers of production and engineering departments. The obtained results allowed recognizing the gap in knowledge about Industry 4.0 and its proper maintenance practices. They can be the basis for shaping programs raising the knowledge and competences of the personnel of enterprises entering and on the path of Industry 4.0 in this respect.